Surrounding rock control technology of large-section open-off cut with composite roof under deep mining conditions: a case study - Xu, Shengji; Zhou, Qingcong; Wang, Kangjie (Frontiers in Earth Science, 2025)
This study addresses the critical challenge of maintaining surrounding rock stability in the large-section open-off cuts with composite roofs, using the 11211 working face in Yanchang Petroleum Kekegai Coal Mine as a case study. Through integrated field measurements, theoretical analysis, numerical modeling, and industrial experiments, we systematically examine the failure mechanisms of surrounding rock and propose corresponding control strategies. Key findings include: 1) The composite roof exhibits weak interlayer bonding and undergoes progressive bending-delamination-fracture failure under stress, requiring a high-strength coupled support system. 2) Based on pressure arch theory, we evaluate the damage range of surrounding rock in the open-off cut and derive optimal bolt and anchor cable support parameters. 3) FLAC3D simulations demonstrate significant positive correlations between stress concentration coefficient, displacement, plastic zone height, and open-off cut span. Through eight support case groups and prestress distribution analysis, we determine optimal anchor cable spacing and length. 4) We propose a combined bolt-cable support strategy for large-section open-off cuts with composite roofs. Field tests showed that the roof-floor displacement was limited to 70 mm and lateral convergence was controlled at 44 mm. This support system effectively controls surrounding rock deformation while significantly enhancing structural stability. This research provides theoretical guidance and engineering references for large-section open-off cuts support in similar geological conditions.